(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
A person’s professional competence is focused on spiritual, motivational, intellectual and practical self-development, willpower and emotional self-management. Each member of society has his own interests and abilities, which allows him to develop the personal and professional qualities of a modern specialist,